Displaced Women : Multilingual Narratives of Migration in Europe. - Aiello, Lucia (Cambridge Scholars Publishing, 2014)
The essays included in this volume mostly originate from the conference organised by the editors at Glasgow Women's Library in March 2012. Language, multilingual narratives and interaction between cultures and languages were key themes of the conference. Interdisciplinary and international, the conference, like this edited volume, brought together specialists working in a range of fields and provided an opportunity for exchanges between historians, sociologists, scientists and literary schola ...